Effects of deposition time and counter-electrode size on the fabrication of lscf-sdc carbonate composite cathode for sofc - Baharuddin, Nurul Akidah; Abd. Rahman, Hamimah; Muchtar, Andanastuti; Sulong, Abu Bakar; Abdullah, Huda (Universiti Kebangsaan Malaysia, 2018)
The electrophoretic deposition (EPD) process has shown great potential in the development of cathodes for solid oxide fuel cell (SOFC). This study thus aimed to determine the feasibility of the electrophoretic deposition technique in producing composite cathode films. Two parameters were investigated, namely, the effects of counter electrode size and those of deposition time on the thickness and quality of an LSCF-SDC carbonate cathode composite deposited onto an SDC carbonate substrate. The effects of the changed parameters were observed by applying constant suspension pH and voltage. Five different deposition times ranging from 10 to 30 min were selected. The counter electrode sizes used were 25 × 25 mm2 and 50 × 50 mm2 . Then, the cathode composite films were sintered at 600°C for 90 min. Microstructural characterization and film thickness measurement were performed using a scanning electron microscope (SEM). The 50 × 50 mm2 counter electrode was found to produce a cathode composite film with higher thickness. The effects of the selected parameters (deposition time and counter electrode size) were also determined by analyzing the weight and thickness of the obtained LSCF-SDC carbonate films. The results showed that for the selected time interval, a film thickness of 4.6 to 30.8 μm is generated. Further studies on fabricating LSCF-SDC carbonate cathode composites by electrophoretic deposition present promising potential given that the film thickness obtained agree well with those derived in previous studies on various types of cathode materials.